2020
DOI: 10.1002/adfm.202003317
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Self‐Limiting Structures Engineered with Defective Colloidal Clusters

Abstract: One of the key challenges in the study of self-assembly with synthetic particles is how to build finite-sized constructs that resemble self-limiting structures such as well-known proteins and biomolecules found in nature. Inspired by this concept, a novel method for realizing self-limiting selfassembly of colloidal clusters by establishing design rules to obtain desired final structures using a bottom-up assembly approach is presented. The constructs identified in this work will be "locked" in a well-defined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Colloid science and self-assembly have a range of open challenges that require access to building blocks with many orthogonal, tunable interactions to be addressed, such as the self-assembly of finite-sized structures of arbitrary shapes and sizes 5,19,38,39 and understanding the nucleation and growth of multi-component crystals. 17,40 DNA-coated particles are convenient building blocks to address these challenges because their DNA-hybridization-mediated interactions enable on the order of 100 orthogonal interactions 41 with tunable strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Colloid science and self-assembly have a range of open challenges that require access to building blocks with many orthogonal, tunable interactions to be addressed, such as the self-assembly of finite-sized structures of arbitrary shapes and sizes 5,19,38,39 and understanding the nucleation and growth of multi-component crystals. 17,40 DNA-coated particles are convenient building blocks to address these challenges because their DNA-hybridization-mediated interactions enable on the order of 100 orthogonal interactions 41 with tunable strengths.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patchy colloidal clusters can be co‐assembled with spherical particles, [ 93 ] or colloidal clusters as well as other types of patchy clusters to prepare more complex colloidal structures. Figure 10b shows a simple strategy to form different colloidal crystals or the same symmetric one with binary patchy colloidal clusters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patchy colloidal clusters can be co-assembled with spherical particles, [93] or colloidal clusters as well as other types of patchy clusters to prepare more complex colloidal structures. Figure 10b The patchy colloidal cluster can be further developed by varying the size and number of lobes or functionalizing patches in central cores differently with DNA via a post reprogramming process, [83,84,94,95] as shown in Figure 10c.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that DNA-coated particles with differing binding specificities could be prepared from a single feed stock by appending new domains to the DNA on the colloids and that the particles maintained their ability to crystallize after the DNA extension procedure. Colloid science and self-assembly have a range of open challenges that require access to building blocks with many orthogonal, tunable interactions to be addressed, such as the self-assembly of finite-sized structures of arbitrary shapes and sizes [18,40,41,5] and understanding the nucleation and growth of multicomponent crystals [42,29]. DNA-coated particles are a logical choice of building block because their DNAhybridization-mediated interactions enable on the order of 100 orthogonal interactions [43] with tunable strengths.…”
Section: Discussionmentioning
confidence: 99%